Friends with Benefits: An Inside Look of Periodontal Microbes’ Interactions Using Fluorescence In Situ Hybridization—Scoping Review - Esteves, Guilherme Melo (Microorganisms, 2021)
Fluorescence in situ hybridization (FISH) has proven to be particularly useful to describe the microbial composition and spatial organization of mixed microbial infections, as it happens in periodontitis. This scoping review aims to identify and map all the documented interactions between microbes in periodontal pockets by the FISH technique. Three electronic sources of evidence were consulted in search of suitable articles up to 7 November 2020: MEDLINE (via PubMed), Scopus (Elsevier: Amsterdam, The Netherlands), and Web of Science (Clarivate Analytics: Philadelphia, PA, USA) online databases. Studies that showed ex vivo and in situ interactions between, at least, two microorganisms were found eligible. Ten papers were included. Layered or radially ordered multiple-taxon structures are the most common form of consortium. Strict or facultative anaerobic microorganisms are mostly found in the interior and the deepest portions of the structures, while aerobic microorganisms are mostly found on the periphery. We present a model of the microbial spatial organization in sub- and supragingival biofilms, as well as how the documented interactions can shape the biofilm formation. Despite the already acquired knowledge, available evidence regarding the structural composition and interactions of microorganisms within dental biofilms is incomplete and large-scale studies are needed.